„Requiem", czyli testament Stanisława Wyspiańskiego - Żak-Świerczek, Anastazja (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
This paper is devoted to Requiem, a Stanisław Wyspiański’s work from 1901 (published by Dariusz Kosiński in 2010) which, treated marginally until now – as a footnote to the work of the Young Poland artist, is recognized as a full-fledged and relevant work that, in a sense, is central to Wyspiański’s artistic activity and at the same time crowns it. The author places the work between the staging of Dziady according to Wyspiański and his Wyzwolenie, pointing out the key character of the discussed work in the context of considerations referring to the artist’s entire oeuvre. Requiem, read as a dramatic text, also turns out to be an attempt at a total work of art and a realization of the formula of “immense theatre” understood as a combination of greatness and intimacy. Moreover, the manuscript, published posthumously, is a specific artistic testament of Wyspiański.